4th USBED Conference - Demircioğlu, Aytekin (USBED, 2024)
The 4th USBED Conference was held in İstanbul/Türkiye, hosted by İstanbul Topkapı University, on 1-2 November 2024, with the participation of 132 people from 17 countries. 30 of the participants of the conference were from Türkiye and 102 were from different countries. Participants' countries are Albania, Azerbaijan, Georgia, Germany, Greece, Lithuania, India, Indonesia, Jordan, Kingdom of Saudi Arabia, Lebanon, Iran, Malaysia, Pakistan, Türkiye, Ukraine, United Kingdom. A total of 92 valuable papers were presented at the conference. 7 abstracts and 20 full texts, total 27 papers from Türkiye; 27 abstracts and 38 full texts, total 65 papers were published from abroad. The rate of presented foreign papers is 70,66%; The rate of prsented local papers is 29,34%.
Keywords: FOS: Social sciences; Conference; Social sciences